Alternatives to Multilateralism New Forms of Social and Environmental Governance - Partzsch, Lena (Earth System Governance, 2020)
Analysis and case studies of emerging forms of private, public, and hybrid social and environmental governance. The effects of globalization on governance are complex and uncertain. As markets integrate, governments have become increasingly hesitant to enforce regulations inside their own jurisdictions. At the same time, multilateralism has proven unsuccessful in coordinating states' responses to global challenges. In this book, Lena Partzsch describes alternatives to multilateralism, offering analyses and case studies of emerging-alternative-forms of private, public, and hybrid social and environmental regulation. In doing so, she offers a unique overview of cutting-edge approaches to global governance. After laying the theoretical and empirical foundation of her argument, Partzsch presents three case studies from the countries most affected by these new forms of governance. Drawing on primary documents, interviews, and participatory observations, she analyzes cotton supply chains and voluntary (private) cotton certification in Ethiopia; public supply-chain regulation of "conflict resources" from the Democratic Republic of the Congo; and hybrid governance of palm oil production in Indonesia. Partzsch finds that the new entanglement of public and private regulation fails to address social and environmental considerations in mainstream markets; argues that only in exceptional cases do alternative forms of regulation overcome the power asymmetries between actors in the consuming countries of the Global North and those in the producing countries of the Global South; and concludes that, while the paradigm of free trade fades, we must continue to develop viable alternatives in order to pursue collective norms of environmental sustainability and social justice.